(μ-Piperazine-1,4-dicarbodithioato-κ(4) S (1),S (1′):S (4),S (4′))bis[bis(triphenylphosphane-κP)gold(I)] chloroform disolvate - Guzei, Ilia A. (International Union of Crystallography, 2011)
In the title compound, [Au(2)(C(6)H(8)N(2)S(4))(C(18)H(15)P)(4)]·2CHCl(3), the digold complex resides on a crystallographic inversion center and co-crystallizes with two molecules of chloroform solvent. The piperazine-1,4-dicarbodithioate linker has an almost ideal chair conformation. The geometry about the gold atoms is severely distorted tetrahedral punctuated by a very acute S—Au—S bite angle.